Study on the Thermal Kinetics of Baijiao Anthracite Oxidation Induced by Water and Associated Pyrite. Issue 4 (12th March 2023) - Jiang, Zhi-Gang; Duan, Xia-Dan; Bai, Zu-Jin; Xiao, Yang; Wang, Cai-Ping; Deng, Jun
ABSTRACT: Water and pyrite (FeS2 ) in coal have great synergistic effect on coal self-ignite. In order to explore the characteristics of spontaneous combustion of high humidity and high sulfur coal, this paper selected different concentrations of water and pyrite to carry out thermogravimetric experiment and oxidation reaction kinetics analysis. The changes of coal samples oxidation under low temperature in mass and characteristic temperatures were studied through thermogravimetric (TG) analysis. The results indicate that the promoting effect of water on coal spontaneous combustion turns to restrain when it reaches 15%, and water and pyrite have substantial synergistic effect on coal oxygen absorption and mass gain stage ( T 3 – T 5 in TG temperatures), besides there is a range of water/pyrite contents (10–15 mass% water and 2–4 mass% pyrite) that have the largest effect on coal oxidation reactions. Through the analysis of oxidation reaction kinetics, it was found that the change rule of the apparent activation energy ( E a ) in coal oxygen absorption and mass gain stage is similar to that of the thermogravimetric change, and it was the lowest at 2–4 mass% pyrite and 10–15 mass% water content. The reaction process of coal oxidation by water and pyrite conforms to the equation n = 4 Avrami-Erofeev, therefore water and pyrite just can promote coal oxidation externally. This research provides support for further understanding and control the influence of water and associated pyrite on coal self-ignite.